The impact of acute Gastroenteritis on haematological markers used for the athletes biological passport - Report of 5 cases - Schumacher, Y. O.; Pottgiesser, T. (International Journal of Sports Medicine, 2011)
The haematological module of the "Athletes Biological Passport" (ABP) is used to detect blood doping through the longitudinal variation of blood variables, such as haemoglobin concentration (Hb). Sporting federations have opened disciplinary procedures against athletes based on ABP results. Suspicious athletes try to explain the variations in their blood values with dehydration caused by gastrointestinal (GI) problems. The aim of the present report is to describe haemoglobin concentration, a key variable of the ABP, during acute gastroenteritis in athletes. 5 athletes with severe gastroenteritis were studied in retrospective. Blood test results (Hb, white blood cell count (WBC) and differential, CRP) obtained on hospital admission for GI problems were compared to data obtained from the same athletes in states of good health on previous occasions. During GI problems, athletes displayed marked inflammatory constellations with increased CRP and typical WBC shifts. Hb was not affected and remained mostly unchanged. This is in line with basic physiologic fluid regulation, where plasma volume is kept constant, even under conditions of severe dehydration. It is therefore unlikely that fluid loss associated with gastroenteritis will cause athletes blood data to reach levels of abnormality that will be suspicious of blood doping.